Structure‐Activity Relationships of Terpendole E and Its Natural Derivatives. Issue 4 (8th February 2017) - Nagumo, Yoko; Motoyama, Takayuki; Hayashi, Toshiaki; Hirota, Hiroshi; Aono, Harumi; Kawatani, Makoto; Osada, Hiroyuki; Usui, Takeo
Abstract: Terpendole E (TerE) is the first natural product that inhibits mitotic kinesin Eg5 (kinesin spindle protein). Recently, TerE is suggested to have a different binding site and/or inhibitory mechanism than other L5 loop‐binding type Eg5 inhibitors. Here, we report the structure‐activity relationships (SARs) of natural TerE derivatives, including two compounds not reported before. Our SAR results indicated that the paspaline‐like indole‐diterpene skeleton is important for Eg5 inhibition, and that both further oxidation except for 11‐position and further prenylation decreases the Eg5 inhibitory activity. Abstract : Structure‐activity relationship results indicate that the paspaline‐like indole‐diterpene skeleton in terpendole E and its natural derivatives is important for the inhibition of the mitotic kinesin spindle protein Eg5.